ANALISIS KEMANDIRIAN KEUANGAN KABUPATEN DAN KOTA DI PROVINSI NUSA TENGGARA TIMUR TAHUN ANGGARAN 2016-2020 - Nasly Betsyeba Mahalia Loni; Yohana Febiani Angi; Cicilia A. Tungga (Universitas Nusa Cendana, 2022)
This study aims to identify and explain the financial independence of districts and cities in East Nusa Tenggara Province based on financial independence ratio analysis with a quantitative descriptive approach. Data collection was carried out using the documentation method, namely by taking financial data in the form of Budget Realization Reports from 22 Regencies/Cities in East Nusa Tenggara Province in 2016-2020. The results of the study show that the level of independence of districts/cities in East Nusa Tenggara Province Not independent has not even touched half of the highest level of independence, in 2016 the highest independence achieved was the